Rhodium-based metallodrugs for biological applications: current status and future perspectives - Xiang, Wang; He, Suisui; Kuang, Tao; Yin, Jun; Hu, Bin; Sun, Chao; He, Juan; Wang, Jun; Yu, Cui-Yun; Wei, Hua (Materials today bio, 2025)
Metal complexes represent a promising avenue in drug research and development, exemplified by metallodrugs including cisplatin, carboplatin, and oxaliplatin that have been clinically approved for the treatment of various solid tumors. However, most of the reported metallodrugs suffer from compromised therapeutic efficacy due to multidrug resistance (MDR) and severe systemic toxicity. Rhodium is another useful member of the platinum group metals in addition to the extensively explored platinum, whose complexes have attracted increasing attention in bioinorganic and medicinal chemistry not only for their low oxophilicity, broad functional-group tolerance, and superior catalytic performance, but also for their intriguing self-assembly behaviors and photophysical properties arising from the intermolecular metallophilic interactions. Together with the tremendous progresses made in the nanotechnology and biotechnology, targeted delivery of rhodium-based metallodrugs to lesion sites in either a passive or active means, or via a biomimetic strategy enables state-of-the-art approaches with great therapeutic efficiency. Nonetheless, there remains a critical lack of comprehensive reviews with a focus on rhodium complexes and their nanodrug derivatives. Here we systematically summarize the existing research on this hot subject of research, and provides a dynamic in-depth overview of the design and development of rhodium complexes and rhodium-containing nanomaterials across various medicine fields, including biomedical imaging, cancer therapy, antibacterial treatments, and anti-inflammatory applications. Critical evaluations are performed on the current challenges and future prospects of this rapidly developing field, for the purpose of promoting a thorough understanding of the latest advancements and further inspiring upcoming notable studies. [Display omitted]